Analyzing Serum Level Changes in Dehydroepiandrosterone Sulfate, Dihydrotestosterone, Progesterone, and Prolactin after Radioactive Iodine Treatment for Papillary Thyroid Carcinoma - Mehrosadat Alavi; Mohammad Atefi; Farzaneh Raeisi (Iranian Journal of Medical Physics)
Introduction: Effective treatment of papillary thyroid carcinoma (PTC) is total thyroidectomy which is followed by radioactive iodine therapy (RIT) to ablate pathologic thyroid remnants and treat metastatic tumors. However, there are concerns about possible side effects of RIT on different hormones that are important in different aspects including the immune defense system, cardiovascular system, pregnancy, and reproductive health. This study aimed to assess the impact of RIT on reliable hormonal markers levels including dehydroepiandrosterone sulfate (DHEA-S) and dihydrotestosterone (DHT) in men as well as progesterone and prolactin in women undergoing treatment for PTC. Material and Methods: 60 patients (30 male and 30 female) who underwent total thyroidectomy due to PTC and aged 25-50 were selected using convenient sampling. Blood samples were collected from each PTC patient before and 60 days after RIT. DHEA-S, DHT, progesterone, and prolactin concentrations were quantified using an enzyme-linked immunosorbent assay kit. The paired t-test was conducted to compare hormonal marker levels before and after RIT. Results: Our data revealed significant decreases in DHEA-S and DHT levels between pre- and post-RIT (P< 0.001). In contrast, progesterone and prolactin levels increased significantly after RIT (P< 0.001). Conclusion: The levels of DHEA-S, DHT, progesterone, and prolactin, which reflect testicular and ovarian reserves, were found to change after RIT. The levels of DHEA-S, DHT, progesterone, and prolactin, which reflect testicular and ovarian reserves, were found to change 60 days after RIT. Despite its benefits in treating PTC, RIT can have serious adverse effects including changes in the serum levels of sexual hormones. Materials and Methods: 60 patients (30 male and 30 female) who underwent total thyroidectomy due to PTC and aged 25-50 were selected using convenient sampling. Blood samples were collected from each PTC patient just before and 60 days after RIT. The concentrations of DHEA-S, DHT, progesterone, and prolactin were quantified using an enzyme-linked immunosorbent assay kit. The paired t-test was conducted to compare hormonal markers levels before and after RIT. Results: Our data revealed significant decreases in DHEA-S and DHT levels between pre-and post-RIT (P< 0.001). In contrast, progesterone and prolactin levels increased significantly after RIT (P< 0.001).Conclusions: The levels of DHEA-S, DHT, progesterone, and prolactin, which reflect testicular and ovarian reserves, were found to change after RIT. The levels of DHEA-S, DHT, progesterone, and prolactin, which reflect testicular and ovarian reserves, were found to change 60 days after RIT. Despite its benefits in treating PTC, RIT can have serious adverse effects including changes in the serum levels of sexual hormones.